Association of Self-Reported Hearing Difficulty to Objective and Perceived Participation Outside the Home in Older Community-Dwelling Adults. (February 2015) - Mikkola, Tuija Maria; Portegijs, Erja; Rantakokko, Merja; Gagné, Jean-Pierre; Rantanen, Taina; Viljanen, Anne
Objective: To investigate whether hearing difficulty is associated with objective and perceived participation in social and leisure activities outside the home in older adults.Method: Self-reported hearing difficulty, frequency of participation, perceived participation and Mini-Mental State Examination (MMSE) were obtained from 848 community-dwelling men and women aged 75 to 90.Results: Among persons with MMSE ≤ 24, hearing was not associated with participation. In persons with MMSE > 24, relative to persons who reported no difficulty hearing, participants with major hearing difficulty had a higher odds ratio [OR] for infrequent participation in group activities (OR 2.1, 95% confidence interval [CI] [1.2, 3.6]) and more restricted perceived participation (OR 2.1, 95% CI [1.2, 3.7]). Participants with and without hearing difficulty did not differ in their frequency of attending non-group activities or meeting (grand)children or acquaintances.Discussion: Hearing difficulty may restrict older adults with normal cognition from participating in social and leisure activities and living their life as they would like to outside the home.